English teachers' perceptions of challenges and responsibilities in schools related to the implementation of the Merdeka Curriculum - Merlina Halawa (Institut Nalanda, 2024)
This study examines the perceptions of English teachers in Indonesian schools on the challenges and responsibilities of implementing the Independent Curriculum, a student-centered education reform initiative. Using a mixed methods approach including surveys and semi-structured interviews, the study examined teachers' understanding of the curriculum, their experiences of implementing it, and their concerns and suggestions for improvement. The results show both positive and negative perspectives. Teachers recognized the potential of the course to promote autonomous and personalized learning among students but also highlighted challenges related to workload, resource constraints and professional development needs. The study highlights the importance of supporting teachers through capacity building and collaborative practice to ensure successful implementation of independent courses and optimize their benefits for Indonesian English learning